Kinerja Pelaksanaan Jaminan Sosial Oleh BPJS Kesehatan di Kota Manado - Trifena Julia Kambey; Yoan Barbara Runtunuwu; Mario Randy Lengkong; Kris Tumbel (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Public services provided by the Social Security Administering Agency (BPJS) Health sometimes encounter obstacles in providing services to the community with a dividing wall between the service provider and the service recipient in the form of restrictions on the number of people even in the midst of world conditions in general and Indonesia in this case the people of Manado city in particular. This study examines the quality of Public Services at the Manado City Social Security Administering Agency. That the form of service at the Manado City BPJS Health is in the form of a form of service provided to participants. To access services at the Manado City BPJS Health can be done in two ways, namely online and offline. The reliability of the service provided by the city BPJS Health is the ability of employees to provide services at the Manado City BPJS Health. This is also influenced by the quality of human resources owned by the Manado City BPJS Health. The responsiveness of the service at the Manado City BPJS Health is an effort to respond to every problem faced by BPJS customers in accessing services. The service guarantee in BPJS Health can be seen from every information given to the public, whether it is about time or other services, and also BPJS Health City always refers to every policy made by the government in terms of BPJS contributions. Empathy given by BPJS Health Manado City to service users is part of its operational standards